2011
DOI: 10.1159/000331008
|View full text |Cite
|
Sign up to set email alerts
|

Is Neuropathy Involved with Restless Legs Syndrome in Machado-Joseph Disease?

Abstract: Objective: To evaluate a group of spinocerebellar ataxia type 3 (SCA3) or Machado-Joseph disease (MJD) (SCA3/MJD) patients and assess whether there is an association between neuropathy and serum ferritin levels and restless legs syndrome (RLS). Methods: Twenty-six SCA3/MJD patients underwent electromyography studies to check for neuropathy. Their serum ferritin levels were measured as well. These findings were evaluated based on the presence or not of RLS and its severity. Results: The proportion of neuropathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(26 reference statements)
0
9
1
1
Order By: Relevance
“…Furthermore, there are clinical, imaging and anatomopathological evidence that basal ganglia and substantia nigra degeneration may occur in MJD patients [23][24][25]. Previous studies have tested different hypothesis for RLS in MJD, a correlation between neuropathy and ferritin levels, but they were not conclusive [10,22]. Our data failed to show a significant correlation between RLS, RLS severity, RWA, RBD and RBD severity with DAT densities.…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, there are clinical, imaging and anatomopathological evidence that basal ganglia and substantia nigra degeneration may occur in MJD patients [23][24][25]. Previous studies have tested different hypothesis for RLS in MJD, a correlation between neuropathy and ferritin levels, but they were not conclusive [10,22]. Our data failed to show a significant correlation between RLS, RLS severity, RWA, RBD and RBD severity with DAT densities.…”
Section: Discussioncontrasting
confidence: 82%
“…Interestingly, higher risk of falls was not evidenced in SCA6 patients, probably because they present a pure presentation with late onset of symptoms. It must be borne in mind that each SCA type has different neurological signs and symptoms associated with ataxiafor instance, neuropathy and ophthalmoparesis in SCA2 and SCA3, pyramidal signs in SCA1, and dystonia, and other extrapyramidal signs in SCA3 [19][20][21][22] . Therefore, we hypothesized that there will be differences in balance impairment and ability to function in different SCA types.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological mechanisms related to RLS in MJD are still unclear. Some data failed to demonstrate a correlation with neuropathy, ferritin levels, or substantia nigra echogenicity . A recent study demonstrated that the severity of RLS in patients with MJD may be influenced by nigral iron load reflected by substantia nigra echogenicity .…”
Section: Main Non‐motor Symptoms and Extra‐cerebellar Signs Already Dmentioning
confidence: 99%
“…PN in MJD has long been known and may be the presenting manifestation of the disease . Previous estimates indicate that 60% of all patients ultimately develop clinical signs of PN .…”
Section: Main Non‐motor Symptoms and Extra‐cerebellar Signs Already Dmentioning
confidence: 99%